Diagnosis of Mycobacterium abscessus/chelonae complex cutaneous infection: Correlation of tissue culture and skin biopsy. (19th December 2019) - Sardiña, Luis A.; Kaw, Urvashi; Jour, George; Knabel, Daniel; Dyck, Rayna M.; Procop, Gary W.; Bergfeld, Wilma F.; Harrington, Susan; Demkowicz, Ryan; Piliang, Melissa P.
Abstract: Mycobacterium abscessus and M . chelonae belong to the rapid‐growing nontuberculous mycobacteria (NTM) group, which are defined by their ability to form visible colonies on agar within 7 days of subculture. Cutaneous infections by this complex show a heterogeneous clinical presentation with varied histopathologic findings. However, the presence of vacuoles in many specimens has been reported as a specific histologic finding. Herein, we correlate the histopathology of patients with tissue‐culture positive M . abscessus / M . chelonae complex in order to identify features that may prompt a rapid categorization of the infectious etiology. The cohort includes 33 skin punch biopsy specimens from 28 patients who had associated positive tissue cultures. The most frequent clinical presentation was a single or multiple nodule. Twenty‐seven specimens (81.81%) were found to have vacuoles. The observation of certain histologic features (ie, polymorphonuclear microabscesses and epithelioid granuloma formation) should raise the possibility of infection by NTM. In addition to these findings, we believe the presence of vacuoles in the dermal and subcutaneous inflammation should raise suspicion for NTM.